Investigating the controls on greenhouse gas emission in the riparian zone of a small headwater catchment using an automated monitoring system. Issue 5 (20th August 2021) - Wang, Jihuan; Bogena, Heye; Süß, Thomas; Graf, Alexander; Weuthen, Ansgar; Brüggemann, Nicolas
Abstract: Riparian zones as the transition zone between terrestrial and aquatic ecosystems play an important role in C and N cycling and greenhouse gas (GHG) emissions. As such, they may help to mitigate climate change but could also accelerate it, depending on the particular processes affected by changes in the hydrologic regime. Hydrological observations indicated frequent shallow groundwater in the riparian zone, especially near the stream and during the wet winter and spring seasons with consequently frequent occurrence of soil water saturation. The redox potential was mainly governed by the soil water regime: under water saturation conditions, the redox potential of the soil decreased and returned to the oxic state after soil drainage. We found that soil temperature and soil water content were the main drivers of the variations in CO2 fluxes, with highest CO2 emission during summer and the lowest emissions in the winter period (162.2–5.4 mg CO2 –C m −2 h −1 ). The annual average daily N2 O emission rate was low (2.3 μg N2 O‐N m −2 h −1 ), with the highest average daily N2 O emission in March as a result of low temperature and partial soil saturation after heavy precipitation events (37.5 μg N2 O‐N m −2 h −1 ). Our study showed that continuous measurement of redox potential, soil temperature, and soil water content can improve the understanding of GHG emissions in riparian zones. Core Ideas: An automated measurement system was used to capture the soil hydrological parameters and Eh. Eh showed significant spatiotemporal variations due to the hydrological gradients and events. Soil Eh was slightly positively correlated with CO2 . Monthly average CO2 emissions show a negative linear relationship with groundwater table depth. The average Eh at −30 cm has a quadratic relationship with the distance to the stream.